Competitive characteristics of judo: an analysis based on match duration - Sogabe, A.; Maehara, K.; Yamasaki, S. (Association for the Scientific Studies on Judo, Kodokan, 2011)
Objective: This study aimed to demonstrate the competitive characteristics of judo according to sex and weight division by analyzing the duration of matches. Methods: At the 2009 All Japan Selected Judo Championships (Kodokan-cup), we measured the total match duration, frequency and average duration of `ma-te` calls by the referee, and frequency and average duration of `ne-waza` for each match then compared the results of each division. Results/ Discussion: The average match duration for male competitors was 5 min 20 s ± 2 min 47 s, with a total average match duration for the 6 matches until the final of 32 min. The average match time for female competitors was 5 min 53 s in the 48-57 kg weight divisions, 7 min 41 s ± 2 min 46 s in the 63 kg division, and 4 min 20 s ± 2 min 45 s in the 70-78 kg and over divisions. Female competitors in each of these respective weight divisions were therefore required to compete for a total average duration of 35 min 30 s, 46 min 10 s, and 22 min until the final match. Conclusion: The results of this study show that judo characteristics differ according to sex and weight division. This finding suggests that when implementing training to improve competitive ability in judo, it is essential to adapt programs to meet individual characteristics rather than adopting a one-size-fits-all approach.